2013
DOI: 10.1007/s12663-013-0473-z
|View full text |Cite
|
Sign up to set email alerts
|

Artefacts Produced by Normal Saline When Used as a Holding Solution for Biopsy Tissues in Transit

Abstract: Oral surgeons, surgeons and dentists carrying out small biopsy procedures on an out-patient basis have been frequently sending poorly stored biopsy tissues to the Departments of Oral Pathology of various dental colleges, wherein the tissues were being stored in normal saline and then transferred to formalin. Such tissues often show abnormal cellular and architectural changes, which pose a challenge to diagnosis, especially when the histopathologist is not aware that the tissue was stored in normal saline for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…19,32 Fixation stops these chan ges. 19,32,33 It maintains the integrity of cells and their chemi cal components, 34 preserving the tissue in conditions like when alive. 13,34 The time interval between the surgical removal of the sample and its immersion in a proper fix ative is referred to as the ischemia or hypoxia time, 34,35 which is associated with the activation of tissue enzymes, autolysis, and the degradation of proteins, DNA and RNA.…”
Section: Artifacts Due To a Delay In Fixationmentioning
confidence: 99%
See 3 more Smart Citations
“…19,32 Fixation stops these chan ges. 19,32,33 It maintains the integrity of cells and their chemi cal components, 34 preserving the tissue in conditions like when alive. 13,34 The time interval between the surgical removal of the sample and its immersion in a proper fix ative is referred to as the ischemia or hypoxia time, 34,35 which is associated with the activation of tissue enzymes, autolysis, and the degradation of proteins, DNA and RNA.…”
Section: Artifacts Due To a Delay In Fixationmentioning
confidence: 99%
“…34 Tap water, 3 distilled water or saline are occasionally used for tissue fixation. 18,20,33 Tissues fixed with these solutions often show abnormal cellular or structural changes 33 that can pose a challenge for the correct diag nosis of the lesion. 33 Saline does not cause any fixation at all 19 and should not be used even for a short time.…”
Section: Artifacts Due To the Type Of Fixative Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that if biopsy is placed in saline for 1 h, and then transferred to formalin fixative, distortion of tissues (cell vacuolization in basal layer of epithelium and reduced cohesiveness of collagen fibers in the connective tissue) take place, making the diagnosis problematic. [5] In case the dental surgeon believes that immunofluorescence would be necessary (for vesiculobullous lesions and/or autoimmune disorders), it is better to take two tissue samples: one in formalin for routine staining and the other in Michel's solution for direct immunofluorescence. [6] The container should be tightly sealed and properly labeled with patient's name, age, gender and site.…”
Section: For Most Diagnoses All That Is Needed Is An Ounce Of Knowledmentioning
confidence: 99%